Agents of dreamland - Kiernan, Caitlín R. (Kiernan, Caitlín R. Tinfoil dossier, 2017)
A government special agent known only as the Signalman gets off a train on a stunningly hot morning in Winslow, Arizona. Later that day he meets a woman in a diner to exchange information about an event that happened a week earlier for which neither has an explanation, but which haunts the Signalman. In a ranch house near the shore of the Salton Sea a cult leader gathers up the weak and susceptible <U+2014> the Children of the Next Level <U+2014> and offers them something to believe in and a chance for transcendence. The future is coming and they will help to usher it in. A day after the events at the ranch house which disturbed the Signalman so deeply that he and his government sought out help from <U+2018>other<U+2019> sources, Johns Hopkins Applied Physics Laboratory abruptly loses contact with NASA's interplanetary probe New Horizons. Something out beyond the orbit of Pluto has made contact. And a woman floating outside of time looks to the future and the past for answers to what can save humanity.